If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -1 = 3y + 13 Reorder the terms: -1 + 5y = 3y + 13 Reorder the terms: -1 + 5y = 13 + 3y Solving -1 + 5y = 13 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -1 + 5y + -3y = 13 + 3y + -3y Combine like terms: 5y + -3y = 2y -1 + 2y = 13 + 3y + -3y Combine like terms: 3y + -3y = 0 -1 + 2y = 13 + 0 -1 + 2y = 13 Add '1' to each side of the equation. -1 + 1 + 2y = 13 + 1 Combine like terms: -1 + 1 = 0 0 + 2y = 13 + 1 2y = 13 + 1 Combine like terms: 13 + 1 = 14 2y = 14 Divide each side by '2'. y = 7 Simplifying y = 7
| 7/12x-7/6x^2 | | 117=2x^2+7+61-x^2 | | 6y-24=12 | | 7n+21+n=37 | | 5x=65+x | | 6-(x+4)=12 | | 6y+4x=20 | | (3z-1)-(z+2)=15 | | 1.75x+0.65=10 | | 1.75-0.65x=10 | | -3e=9e+7 | | 2x1/2=9/8 | | X^2-12x-3=14 | | 3ax+1=16 | | 0.4=.40 | | 5y=16[8] | | 36=2x+y | | z/7-3=2 | | x^2-33= | | -8(6x-2)+7(7x-7)-7=6-2 | | u/11=6 | | 11w=8470 | | -[7x+(6x+1)]=4-(5x+8) | | 6x^2-12x-51=-3 | | t+12=24 | | -4ln(x)+2x+6=0 | | 3tanx-5=4 | | 5k^2+12k+4= | | cos^2x+4cosx-5=0 | | 1000000/5-100000*3/30/2-470 | | 4x^2+6x-28=0 | | 10x^2-15x-70=0 |